Metodologia de superfície de resposta para análise do dimensionamento de um sedimentador continuo a partir de experimentos em proveta - Vieira, Erika Suellen Dos Santos (Universidade Federal do Tocantins, 2022)
The sizing of continuous decanter can be done from experimental data obtained in laboratory tests to know the characteristics of the suspension, as there are factors that influence sedimentation, such as the concentration of solids and the area available for operation. Discontinuous sedimentation information serves as a basis for the design of continuous decanters, allowing the construction of sedimentation curves, and later the application of mathematical models for the calculation of design variables. The objective of this work was to size the area of a continuous decanter applying the mathematical models of Kynch (1952), Talmagde and Fitch (1955) and Biscaia Junior (1982). In order to determine the best operating conditions to obtain the calcium carbonate suspensions to be analyzed, was used the Central Rotatable Composite Design (CRCD), and the results obtained were evaluated applying the Response Surface Methodology (RSM), in order to observe the effect of the concentration of the suspension and the diameter in the calculation of the area. Based on the conditions established in the present study, it was concluded that the sedimentation curves constructed had excellent correlation coefficients, with values between 0.9437 and 0.999, attesting that the experimental data provide reliability for the design of a continuous decanter. Applying the mathematical models of Kynch (1952) and Biscaia Junior (1982) found variations of very similar areas, between 9 to 60 m2 and 11 to 72 m2, respectively. The Talmagde and Fitch method resulted in values ranging from 5 to 18 m2 and presented the most adequate modeling, indicating that approximately 90% variations are explained by the adjusted model (A = 12,450 + 4,105x1/2 + 4,215 x2 − 5,001x2/2). In general, when the interaction effect is not significant, as in the case of the three methods analyzed, it is possible to affirm that they are independent factors, where each main effect can be interpreted in isolation.